Ice age tropical South America: What was it really like? - Scientific note - Hammen, T. van der (Amazoniana, 2001)
Is an honest and respectful analysis of the status of the various theories proposed to explain aspects of Arnazonian biodiversity and biogeography using the data provided by colleagues specializéd in other fields. Honest disagreements may exist on the conclusions because of the uncertainty created by the fact that nobody was present to see what really happened in the distant past.
Keywords: Biogeografia Amazônica